A comparative study of China's foreign direct investment in Africa: regulation, policy, and legal cooperation - Lefifi, Tebogo (Department of Commercial Law, 2024)
A new era of Africa-China legal cooperation in Foreign Direct Investments (FDI) was inaugurated following the successful founding of The Forum on China Africa Cooperation (FOCAC) in 2000. In 2015, China became a capital exporter and adopted a new global strategy to reverse the hegemony comprising norm-making and advising law reforms in developing countries. However, a comprehensive approach is still lacking to determining and understanding the potential impact and influence of China's outbound FDI (OFDI) policy, laws and regulations on Africa's economic development agenda and legal environment. Previous research has interpreted China's increasing outward foreign direct investment OFDI as a byproduct of China's market- or resource-seeking agenda and failed to consider the legal aspects of the relationship. Contrarily, this study argues that China's OFDI influence introduces a novel type of south-south legal transplant that will shape prospective African legislative initiatives, ideologies, and norms. By examining China' legal transplant experience and FDI governance model ideology, this research aims to provide a comprehensive understanding of China's influence on Africa's future legal reforms. The analysis explicitly explores Africa's transplant of China's cyber sovereignty governance model. The study utilises a desktop research study methods using a combination of primary and secondary sources. The data is gathered from research from various sources in official government websites, action plans documents, academic literature, and case studies. A comparative analysis of the benefits and drawbacks of China's and Africa's experiences with FDI regulation and legal transplant are key considerations to the study. The findings of the study reveal and highlight the benefits and challenges of legal cooperation through OFDI and present recommendations for the development of laws with Africa-China characteristics. The research will guide Africa's policy response to regulating Chinese investments in the Continent and guide lawmakers in transplanting laws from China.